"Anaerobic" critical velocity and swimming performance in young swimmers - Almeida Marinho, D.; Amorim, R. A.; Costa, A. M.; Marques, M. C.; Perez-Turpin, J. A.; Neiva, H. P. (Journal of Human Sport & Exercise, 2011)
Recent studies explored a new trend of critical velocity as a parameter to evaluate and monitor anaerobic training. The aim of this study was to analyse the relationship between anaerobic critical velocity and short distances performances in the four swimming techniques, in young swimmers. 12 male and 8 female swimmers (mean ±SD; age 12.10 ± 0.72 years old) performed maximal 10, 15, 20 and 25 m in the four conventional swimming techniques to determine critical velocity from the distance-time relationship. 50, 100 and 200 m individual best performances of the season were used to compare with the critical velocity assessed. The mean ± SD values of anaerobic critical velocity (m.s-1) were 1.10 ± 0.22, 1.07 ± 0.10, 0.89 ± 0.16 and 1.27 ± 0.16, for butterfly, backstroke, breaststroke and front crawl, respectively. Anaerobic critical velocity was correlated with the 50 and 100 m swimming event velocities in backstroke (r = 0.85; r = 0.86), breaststroke (r = 0.92; r = 0.90) and front crawl (r = 0.85; r = 0.91). Considering the 200 m swimming performance, relationships were found in front crawl (r = 0.90) and in breaststroke (r = 0.89). Differences between anaerobic critical velocity and swimming performance were observed in all swimming techniques for the 50 m and in breaststroke, front crawl and backstroke for the 100m. There were no differences regarding the 200 m swimming performance. These findings suggest that anaerobic critical velocity may be managed as a control parameter and even to prescribe training for young swimmers.